Digitalization of Sports Equipment in Europe: Comparing Wearable Device Use between EU and Non-EU Europe (2024) - URAY, Murat (International Journal of Holistic Health, Sports and Recreation, 2025)
This study compares the use of wearable devices (smartwatches/fitness bands) as a practical indicator of digitalization in sports equipment in the European Union (EU) and non-EU European countries. Eurostat's "Use of Internet of Things by individuals" dataset (isoc_iiot_use; indicator: I_IOT_DCS2—wearables; unit: PC_IND; ind_type: IND_TOTAL) is used for a single year, 2024, and country-level usage rates for individuals aged 16–74 are obtained. In a brief comparative analysis between the EU (EU-27, n=26) and non-EU Europe (n=7), descriptive statistics show that mean usage is 32.8% (sd=9.8; median=30.7%) in the EU and 17.6% (sd=17.5; median=13.0%) in non-EU Europe. The primary Mann–Whitney U test revealed that the difference between the groups was statistically significant (W=158, p=0.0034). The Welch t-test, reported as a robustness check, yielded a borderline result (t=2.21; sd=7.04; p=0.062). Effect sizes were high (Cliff’s δ=0.74; Hedges’ g=1.27; 95% CI 0.37–2.17). The findings indicate that, in terms of technology management, digitalization in the EU has reached a more mature level with complementary assets (connectivity infrastructure, application/service ecosystem, data governance, and regulatory framework). In non-EU Europe, due to heterogeneity, market creation and localization strategies are important.